Data management in cloud, grid and P2P systems 5th International Conference, Globe 2012, Vienna, Austria, September 5-6, 2012. proceedings - Hameurlain, Abdelkader (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on Data Management in Grid and Peer-to-Peer Systems, Globe 2012, held in Vienna, Austria, in September 2012 in conjunction with DEXA 2012. The 9 revised full papers presented were carefully reviewed and selected from 15 submissions. The papers are organized in topical sections on data management in the cloud, cloud MapReduce and performance evaluation, and data stream systems and distributed data mining.